2018
DOI: 10.1002/chem.201804897
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Sided Competitive Axial Coordination of G‐Quadruplex/Hemin as Molecular Switch for Imaging Intracellular Nitric Oxide

Abstract: Axial coordinationi sacrucial biological process to regulate biomolecules' functions in natural enzymes. However,i ti sagreat challenge to determine the single or dual axial interaction between the metal centero fe nzymes and the ligand.I nt his work, ac ontrollable axial coordination system was developed based on G-quadruplex/ hemin complexb yd esigning as eries of fluorescent derivatives. The mechanism on axial coordination of G-quadruplex/hemin with coumarin-imidazolel igandsw as proposed to be single-sided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Therefore, AuNP conjugated with a fluorescent moiety through a biomolecule-responsive linker allow the specific and local release of the dye for turning on the probe’s signal in fluorescence imaging. This concept has been used to image a wide array of biomolecules with AuNP based nanoprobes, namely, pH, , ROS, , proteins, enzymes, , RNA, metal ions, , and other metabolites. , Intracellular pH regulation is critical to living cells and can be used as one of the hallmarks of cancer metabolism for early diagnosis . Recently, several studies have demonstrated the possibility of imaging pH variations at the cellular level using engineered AuNP based nanoprobes. For example, Yu et al constructed a pH-sensitive AuNP functionalized with fluorescent dyes, one responsive to acidic pH and the other to basic pH, and such a system can be used for mapping brain pH variations very finely using fluorescence imaging .…”
Section: Activatable Aunp Based Nanoprobesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, AuNP conjugated with a fluorescent moiety through a biomolecule-responsive linker allow the specific and local release of the dye for turning on the probe’s signal in fluorescence imaging. This concept has been used to image a wide array of biomolecules with AuNP based nanoprobes, namely, pH, , ROS, , proteins, enzymes, , RNA, metal ions, , and other metabolites. , Intracellular pH regulation is critical to living cells and can be used as one of the hallmarks of cancer metabolism for early diagnosis . Recently, several studies have demonstrated the possibility of imaging pH variations at the cellular level using engineered AuNP based nanoprobes. For example, Yu et al constructed a pH-sensitive AuNP functionalized with fluorescent dyes, one responsive to acidic pH and the other to basic pH, and such a system can be used for mapping brain pH variations very finely using fluorescence imaging .…”
Section: Activatable Aunp Based Nanoprobesmentioning
confidence: 99%
“…130 Therefore, AuNP conjugated with a fluorescent moiety through a biomolecule-responsive linker allow the specific and local release of the dye for turning on the probe's signal in fluorescence imaging. This concept has been used to image a wide array of biomolecules with AuNP based nanoprobes, namely, pH, 131,132 ROS, 133,134 proteins, 135 enzymes, 136,137 RNA, 138−140 metal ions, 141,142 and other metabolites. 143,144 Intracellular pH regulation is critical to living cells and can be used as one of the hallmarks of cancer metabolism for early diagnosis.…”
Section: ■ Activatable Aunp Based Nanoprobesmentioning
confidence: 99%
“…2) [5][6][7][8] . The exquisite interaction between G4s and hemin (iron (III)-protoporphyrin IX) results in peroxidasemimicking G4-DNAzyme systems 9 , which have been used as biosensors 10,11 and biodevices 5,12,13 .…”
mentioning
confidence: 99%
“…Under these conditions, full conversion could be obtained by continuous milling (Figures S1–S5). As for hydrazones 1 and 2 , the mechanochemical preparation of fluoresceine‐tagged aminohydantoin 3 (Scheme 1) presents several advantages compared to similar solution‐based experimental procedures: [3g] (a) the use of a base to generate the more nucleophilic free amine can be avoided (reagent economy), the activation being provided by mechanochemical shocks between the reactants; (b) the reaction kinetics is improved (time economy), with full conversion of the starting materials obtained in only 150 min (instead of 24 h); (c) the experimental set‐up was simplified and no dry conditions were needed; (d) the throughput of the process and its ecological footprint were improved, the recovery of the final product being achieved by simply precipitating in water the thiourea 3 (waste economy), with only water and hydrochloric acid generated as by‐products of the reaction and with higher yield (93 %) compared to solution‐based procedures involving click‐type amine‐isothiocyanate coupling reaction (62–70 %) [40,41] …”
Section: Resultsmentioning
confidence: 99%